(untitled) (Kinesiology, 2018)
Objective: The aim of this study was to compare muscle oxygenation of the vastus lateralis during a high volume, isokinetic resistance exercise protocol (HVP) between young adult (YA) and middle-aged adult (MA) men. Methods: Twenty recreationally trained men were assigned to either the YA (21.8±2.0 y, 90.7±11.6 kg, 179±4.7 cm) or MA (47.0±4.4 y, 96.1±21.6 kg, 177±7.7 cm) group. The HVP consisted of eight sets of 10 repetitions of unilateral isokinetic concentric knee extension and eccentric knee flexion at 60°·sec-1. Changes in tissue hemoglobin saturation index (TSI), tissue oxygenated hemoglobin concentration (O2Hb), deoxygenated hemoglobin (HHb), and muscle oxidation index (O2Hb-HHb) were measured during the exercise session using near-infrared spectroscopy (NIRS). Data were analyzed using two-way mix factorial analyses of variance. Results: Prior to exercise, TSI was significantly greater for YA compared to MA (73.2±3.4% vs. 68.6±4.8%, p=0.024). For both groups, significant decreases in O2Hb and O2Hb-HHb, and increases in HHb were observed during each of the eight sets relative to the rest periods (p<0.05). However, the average change during the eight sets of the HVP revealed a significantly higher (p=0.036) level of HHb (7.8±0.5μM vs. 5.3±3.1μM) and a lower (p=0.029) level of O2Hb-HHb (-11.3±1.4μM vs. -7.1±5.5μM) for MA compared to YA. Conclusions: During a high volume, resistance exercise protocol, middle-aged adults experienced reduced muscle oxygen saturation levels compared to younger, recreationally active adults. These results suggest that age-related changes in muscle oxygenation appear to occur in middle-aged adults, regardless of recreational exercise training experience.